On the morphology of the juvenile stages of Ampulex compressa (Fabricius 1781) (Hymenoptera, Ampulicidae) - Fox, Eduardo Gonçalves Paterson [UNESP]; Buys, Sandor Cristiano; Mallet, Jacenir Reis Dos Santos; Bressan-Nascimento, Suzete (My University, 2006)
Ampulex compressa is a cockroach-hunting ampulicid wasp. In this survey we describe its egg, mature larva, along with the 1st and 2nd larval instars and cocoon, with emphasis on the characters considered important to the phylogeny of apoid wasps. It shares the following traits with the Sphecidae: reduced head setae, absence of antennal papilla, three antennal sensilla on antennal orbit, broad and strongly emarginate labrum, and spinneret with prominent raised lips. In common with other Ampulicidae, it has integument of the body granulose and without setae, mandibles with four or five teeth and lacking basal setae, maxillary palp larger than galea and discrete parietal bands. Distinct from the other Ampulicidae, it has a deep median longitudinal groove in the area above the salivary lips, a distinct group of five sensilla on the subgenal area, and lacks spines on the spiracular peritreme. Copyright © 2006 Magnolia Press.
Keywords: Ampulicidae; Hymenoptera; Larval description; Phylogeny; Sphecidae; Ampulex compressa; Apoidea; Blattaria